Splenoportography - Silva García, Ernesto (Cirugía del Uruguay, 1973)
The paper presents splenoportography and kinematic study through cineradiology in the evaluation oZ circulation time in the different syndrome of portal hypertension and introduces anesthesia of the phrenic nerve. Series are rapid and injection is made through automatic pneumatic pump. The normal aspect is shwon and compared with the different obstacles to splenoportal circulation at the different levels: splenic, extrahepatic portal, intrahepatic and suprahepatic.